1997
DOI: 10.1097/00005131-199711000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Transolecranon Fracture-Dislocation of the Elbow

Abstract: Anterior elbow dislocations occur most often as a fracture-dislocation in which the distal humerus is driven through the olecranon, thereby causing a complex, comminuted fracture of the proximal ulna. This injury is frequently confused with anterior Monteggia lesions by virtue of the readily apparent radiocapitellar dislocation. Stable restoration of the appropriate contour and dimensions of the trochlear notch of the ulna will lead to a good result in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
140
1
9

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 201 publications
(155 citation statements)
references
References 27 publications
4
140
1
9
Order By: Relevance
“…Tension-band wiring of the olecranon is thought to be inadequate fixation of an anterior olecranon fracture-dislocation in an adult, and, on the basis of the need for revision surgery in the only patient treated with tension-band wiring in our series, the same may be true in children 10 . We speculate that the added instability of the associated soft-tissue injury makes tensionband wiring insufficient, and plate-and-screw fixation seems preferable.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…Tension-band wiring of the olecranon is thought to be inadequate fixation of an anterior olecranon fracture-dislocation in an adult, and, on the basis of the need for revision surgery in the only patient treated with tension-band wiring in our series, the same may be true in children 10 . We speculate that the added instability of the associated soft-tissue injury makes tensionband wiring insufficient, and plate-and-screw fixation seems preferable.…”
Section: Discussionmentioning
confidence: 70%
“…In other words, this is primarily an ulnohumeral fracture-dislocation rather than a radioulnar fracture-dislocation. Fracture of the coronoid occurs in half of the adult patients with an anterior olecranon fracture-dislocation 10 , but it has not been observed in children with this injury pattern.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…1,26,27 Ring et al 28 and Teasdall et al 29 reported that patient compliance, fracture comminution and extension into the ulnar diaphysis or coronoid process, concomitant radial head fracture and elbow instability may lead to inferior results. On the other hand, Villanueva et al 10 noted that fracture comminution does not necessary have a harmful effect on both clinical and radiological outcome.…”
Section: Discussionmentioning
confidence: 99%